Pertumbuhan dan Hasil Tiga Varietas Kacang Tanah pada Jarak Tanam dan Macam Pengendalian Gulma - Kharis Triyono; P Priyono; Wahyu Agustina (Fapetrik-UMPAR, 2021)
This study aimed was to find an integrated technology to obtain optimum spacing and effective weed control on various varieties based on the peanut yield approach. The design used was a Completely Randomized Block Design arranged in a factorial manner, consisting of 3 factors: Factor 1, plant spacing of 30 x 10 cm, and 40 x 10 cm. The second factor was the type of weed control, which was weeded twice at 21 and 42 days after planting, and the use of the herbicide glyphosate 1.44 kg b.a per hectare. The third factor is the variety of peanuts, namely the Jepara, Kelinci, and Panter varieties. All treatments were repeated 3 times. The data obtained were analyzed by analysis of variance and continued with Duncan's Multiple Distance Test with a significant level of 5%. The results showed that the independent spacing treatment significantly affected all observed parameters. The weed control significantly affected all parameters except seed weight per plot, and varieties treatment significantly affected all parameters except the dry weight of the stover. Interaction between planting distance and weeding type had a significant effect on all observation parameters except the dry weight of the stover.